Rapid agricultural growth is not enough: The Philippines, 1965-80 - Bautista, Romeo M. (International Food Policy Research Institute, 1995)
The Philippine growth experience may be described as a case of agriculture-led development that failed. Rapid agricultural growth during 1965-80 did not translate into sustainable economic growth, and only a small segment of the population benefited to any extent from the observed gains in national income.